The Habitat Analysis of Sunda Clouded Leopard (Neofelis diardi Cuvier 1823) in Batutegi Protection Forest Lampung - Hafiz Nur Malik; Jarwadi Budi Hernowo (Media Konservasi, 2023)
Sunda clouded leopard (Neofelis diardi Cuvier, 1823) is a predator that threatened by habitat fragmentation due to the conversion of forest into residential and agricultural areas. One of the habitats of sunda clouded leopard in Sumatra is in the Batutegi Protection Forest. This research aimed to identify the habitat functions of sunda clouded leopard and its characteristic. Data were collected by direct observation using vegetation plots, line transect, camera trapping, and indirect observation to determine signs of animal activities. Vegetation and canopy openness analysis was used to describe the habitat characteristic, while data of potential prey were analyzed using species diversity and abundance indices. The results show that hunting area for sunda clouded leopard was an area with dense canopy cover (64,67%). Resting area and cover area for sunda clouded leopard were areas with very dense canopy cover (78,64% and 73,43%). Potential prey diversity and abundance with higher rate found in lowland forest (H’=2,35), while the lower rate found in sub-montane forest (H’=1,81).